Palliative Treatment of Obstructive Jaundice in Patients with Carcinoma of the Pancreatic Head or Distal Biliary Tree. Endoscopic Stent Placement vs. Hepaticojejunostomy - Distler, Marius; Kersting, Stephan; Rückert, Felix; Dobrowolski, Frank; Miehlke, Stephan; Grützmann, Robert; Saeger, Hans-Detlev (JOP. Journal of the Pancreas, 2010)
Context Palliative procedures play an important role in the treatment of malignancies of the pancreatic head/distal biliary tree, as only 20-30% can be cured by surgical resection. Objective We sought to determine if surgical or non-surgical management was the most appropriate therapy for the treatment of obstructive jaundice in the palliative setting. Setting High volume center for pancreatic surgery. Patients Analysis of 342 palliatively-treated patients with adenocarcinoma of the pancreatic head or the distal biliary tree. Main outcome measures We studied the outcomes with regard to treatment, complications and survival times. Design The patients were divided into three groups. Group 1: endoscopic bile duct endoprosthesis (no. 138, 56%); Group 2: preoperative stenting followed by laparotomy (if patients were found to be unresectable, palliative hepaticojejunostomy was performed) (no. 68, 28%); Group 3: hepaticojejunostomy without preoperative stenting (no. 41, 16%). We also determined the frequency of re-hospitalization for recurrent jaundice. Results Two hundred and sixty-one (76%) patients showed obstructive jaundice. Mortality in Groups 1, 2, and 3 was 2.2%, 0%, and 2.4%, respectively and morbidity was 5.1%, 17.6%, and 14.6%, respectively. The mean interval between stent exchanges was 70.8 days. Median survival for patients treated only with an endoscopic stent (Group 1) was significantly shorter than that of patients who were first stented and subsequently treated with hepaticojejunostomy (Group 2) (5.1 vs. 9.4 months; P<0.001). Conclusions Hepaticojejunostomy can be performed with satisfactory operative results and acceptable morbidity. Considering that biliary stents can occlude, a hepaticojejunostomy may be superior to endoscopic stenting; hepaticojejunostomy should be especially favored in patients whose disease is first found to be unresectable intraoperatively. Image: Overall survival following endoscopic stent placement and/or palliative surgery.